Pelatihan Pengelolaan Keuangan Keluarga untuk Masyarakat Pedesaan - Azuwandri, Azuwandri; Alfala, Dhika; Hidayah, Nenden Restu (Jurnal Gotong Royong, 2024)
This research discusses the importance of family financial management training for rural communities. Rural communities often face challenges in effectively managing their family finances, due to a lack of necessary knowledge and skills. This training aims to provide a better understanding of how to manage income, organize budgets, and make wise investments. Effective training methods, such as interactive lectures, role plays, and case studies, can be used to improve participants' understanding and skills. By improving financial literacy among rural communities, it is expected to help them make better financial decisions and improve overall family welfare. This article also discusses the challenges that may be faced in delivering financial training in rural areas, including accessibility, culture and economic factors. Further research and sustained efforts are needed to expand the scope of financial training and ensure that rural communities can access the resources they need to improve their financial management.